Relationships among Neighborhood Environment, Racial Discrimination, Psychological Distress, and Preterm Birth in African American Women - Giurgescu, Carmen (J Obstet Gynecol Neonatal Nurs, 2012)
OBJECTIVES: To (a) examine the relationships among objective and perceived indicators of neighborhood environment, racial discrimination, psychological distress, and gestational age at birth; (b) determine if neighborhood environment and racial discrimination predicted psychological distress; (c) determine if neighborhood environment, racial discrimination, and psychological distress predicted preterm birth; and (d) determine if psychological distress mediated the effects of neighborhood environment and racial discrimination on preterm birth. DESIGN: Descriptive correlational comparative. SETTING: Postpartum unit of a medical center in Chicago. PARTICIPANTS: African American women (n(1) = 33 with preterm birth; n(2) = 39 with full-term birth). METHODS: Women completed the instruments 24 to 72 hours after birth. Objective measures of the neighborhood were derived using geographic information systems (GIS). RESULTS: Women who reported higher levels of perceived social and physical disorder and perceived crime also reported higher levels of psychological distress. Women who reported more experiences of racial discrimination also had higher levels of psychological distress. Objective social disorder and perceived crime predicted psychological distress. Objective physical disorder and psychological distress predicted preterm birth. Psychological distress mediated the effect of objective social disorder and perceived crime on preterm birth. CONCLUSION: Women’s neighborhood environments and racial discrimination were related to psychological distress, and these factors may increase the risk for preterm birth.